Mushash 163, Jordanien. Die Grabungskampagnen 2015/2016 // Die lithischen Kleinfunde - Bartl, Karin; Rokitta-Krumnow, Dörte (e-Forschungsberichte des DAI, 2017)
Fieldwork in 2015/2016 (K. Bartl)The Neolithic site Mushash 163 in the western desert steppe (badia) of Jordan has been investigated since 2014 in cooperation with the Department of Antiquities of Jordan. During the excavations in the years 2015 and 2016, four round structures were recorded, which date back to the period between 8800 and 8400 cal BC, that is, the end of the Pre-Pottery Neolithic A (PPNA) (9800–8600 cal BC) and the Early Pre-Pottery Neolithic B (EPPNB) (8600–8300/8200 cal BC). This period, which has been documented rather little in the southern Levant, is of particular importance for the understanding of the process of neolithization, since it is associated with the beginning of domestication in the northern regions of West Asia. The work at the site of Mushash 163 aims to shed new light on this crucial period (of transition) in the southern Levant. The lithic material (D. Rokitta-Krumnow)The site of Mushash 163 is one of the very few Early Pre-Pottery Neolithic B settlements in the Jordanian desert steppe and is investigated since 2014. The main objective is the study of the stratigraphical-chrononological sequence and the structure of this 9th millennium BC site. By evaluating the lithic material, simplified production techniques could be demonstrated, which were applied mainly at household level. The manufacture of special types of tools, for which particular knowledge is required, is comparatively rare. However, the high number of borers in the tool kit indicates a certain specialization in the tool production at the site.